A method for one-step implantation of platinum ions to modify a PEN film

CN122959682APending Publication Date: 2026-10-23KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610844651.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-11
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0012]为解决现有聚合物改性方法需要多步处理、改性层与基体结合力差、难以同时实现静电耗散与抗原子氧侵蚀的问题,本发明的目的是提供一种铂离子单步注入改性PEN薄膜的方法,具体包括以下步骤:

Benefits of technology

(1)本发明以铂离子单步注入改性PEN薄膜,仅需单次注入、无需后续氧化处理,即可同时使PEN薄膜获得106~109Ω/sq的静电耗散表面电阻率及优异的抗原子氧侵蚀性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122959682A_ABST
    Figure CN122959682A_ABST
Patent Text Reader

Abstract

The application discloses a method for modifying a PEN film by single-step platinum ion implantation, and belongs to the technical field of ion beam surface modification of polymer materials. n+ The method comprises the following steps: using a clean PEN film as a target material; using platinum ions (Pt n+ ) as an implant ion source, loading a high-purity platinum metal target into the ion source, starting the ion source, adjusting working parameters, and obtaining a stable beam current; fixing the clean PEN film on a target table in an implantation chamber, starting a mechanical pump and a molecular turbine pump in sequence to perform vacuum pumping; setting implantation parameters, using an electrostatic scanning mode to uniformly scan the ion beam on the surface of the target material; after implantation is completed, the ion source is turned off, and the implantation chamber is cooled to room temperature; high-purity nitrogen is slowly filled into the implantation chamber to reach normal pressure, and a modified PEN film is obtained. The modified PEN film has electrostatic dissipation conductivity and surface atomic oxygen erosion resistance, and is suitable for application scenarios such as flexible solar cell substrates, flexible printed circuits and space environment protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer material ion beam surface modification technology, specifically a method for single-step implantation of platinum ions to modify PEN thin films. Background Technology

[0002] Polyethylene naphthalate (PEN) is a semi-aromatic thermoplastic polyester formed by the condensation polymerization of naphthalene-2,6-dicarboxylic acid and ethylene glycol. Its repeating unit molecular formula is C2. 14 H 10 O4. The naphthalene ring structure of PEN endows it with higher tensile strength, better gas barrier properties, and stronger ultraviolet absorption than polyethylene terephthalate (PET), positioning it between conventional PET films and high-performance polyimide (PI) films. It is widely used in flexible printed circuits (FPCs), flexible solar cell substrates, capacitor insulation, and electrical insulation. However, unmodified PEN films face two key challenges in low Earth orbit (LEO) and geostationary orbit (GEO) environments.

[0003] First, there is the erosion caused by atomic oxygen. Atomic oxygen in the LEO environment is formed by the decomposition of molecular oxygen by the sun's ultraviolet light. When a spacecraft travels at a speed of approximately 8 km / s, the atomic oxygen flux at the windward side can reach 10. 13 ~10 15 atoms / (cm 2 The equivalent impact kinetic energy is approximately 5 eV. Ester bonds (-COO-) in the PEN molecular chain are the primary chemical sites for atomic oxygen attack; ester bond breakage leads to molecular chain degradation and mass loss. PEN is an aromatic polymer containing ester bonds, and it also exhibits severe corrosion in an atomic oxygen environment. Prolonged exposure can cause microporous structures to form on the film surface, resulting in a gradual deterioration of mechanical properties and impacting its on-orbit lifespan.

[0004] Second, there is the issue of electrostatic discharge. PEN thin films have a very high volume resistivity and are electrical insulating materials. In space plasma, the static charge that accumulates on the surface of the thin film cannot be released in time, causing differential charging and discharge breakdown on the surface, which can damage electronic equipment and solar panels on spacecraft.

[0005] Current technologies have proposed different solutions to the above problems, but all of them have obvious drawbacks.

[0006] (1) Coating method: A coating such as SiO2, ITO or fluorinated polymer is applied to the polymer surface to achieve the purpose of resisting proton oxygen or dissipating static electricity. However, there is an abrupt interface between the coating and the polymer substrate. Under the action of thermal cycling stress during orbital operation, cracks and peeling are easily generated due to the difference in thermal expansion coefficients between the coating and the substrate. In addition, the coating method cannot achieve the effects of conductivity and resisting proton oxygen in a single process.

[0007] (2) Blending method: Polyhedral oligomeric silsesquioxanes (POSS) or nanofillers are added during polymer synthesis to improve antigenic oxygen properties. However, this method requires changing the chemical composition of the polymer from the raw material end and cannot be used for post-processing modification of commercially available PEN films.

[0008] (3) Ion implantation method: This method utilizes accelerated ion implantation to alter the surface properties of a material. Existing patents disclose methods for obtaining an oxide protective layer by implanting metal ions such as silicon (Si) and aluminum (Al) onto a polymer surface and then performing an oxidation conversion. While effective, this method requires an additional oxidation conversion step. More importantly, these ions are light ions (Si:Z=14, Al:Z=13), which have a deeper penetration range at the same implantation energy, requiring significant energy to form a sufficient energy deposition density on the surface.

[0009] From a physical perspective, light ions have a smaller mass, which differs significantly from the mass of target atoms. The energy transferred to the target atom in a single nuclear collision is relatively small; therefore, the energy loss is primarily electron energy loss. ) as the main, nuclear deterrence capability ( The low conductivity makes it difficult to generate dense collisional cascades, resulting in limited carbonization efficiency. Furthermore, these light metal ions primarily rely on self-oxidation to generate oxides to acquire antigenic oxygen properties, while the implanted state is usually not fully oxidized. Therefore, additional oxidation conversion steps are often required to form a stable oxide protective layer, making it difficult to simultaneously achieve conductivity and antigenic oxygen properties in a single-step process.

[0010] Existing literature reports various ion implantation modifications of polymers. For example: 150 keV Mg + With a dosage of 1×10 14 ~1×10 16 cm -2 Injection of PET and PEN films showed that both polymers achieved optimal performance at the highest injection rates (1×10⁻⁶). 16 cm -2 The surface resistivity decreased by more than five orders of magnitude, and the G and D peaks of the graphitized structure appeared in the Raman spectrum, confirming that... The formation of a conductive network of carbon clusters. The study also indicates that PEN has slightly higher radiation resistance than PET. Furthermore, there is 1.5 MeV Ag...+ With 1×10¹ 6 cm - ² After injection of polyimide, the surface resistivity drops to approximately 1 × 10⁻⁶. 8 Ω / sq; and 50 keV Ar + Plasma-source ion implantation can reduce the surface resistivity of polyimide by approximately 11 orders of magnitude. The aforementioned work typically optimizes only a single performance metric (conductivity or antigenic oxygen properties), failing to simultaneously meet both requirements in a single-step process.

[0011] Therefore, there is a need in the art for a PEN thin film modification method that is simple to process, does not require subsequent oxidation treatment, and can simultaneously achieve electrostatic dissipative conductivity and antigenic oxygen properties in a single-step injection. Summary of the Invention

[0012] To address the problems of existing polymer modification methods requiring multiple steps, poor adhesion between the modified layer and the substrate, and difficulty in simultaneously achieving electrostatic dissipation and antigenic oxygen erosion, the present invention aims to provide a method for single-step platinum ion implantation modification of PEN films, specifically including the following steps: (1) Target preparation: Polyethylene naphthalate (PEN) film is used as the target material. It is cleaned and dried to obtain a clean PEN film.

[0013] (2) Ion source preparation: using platinum ions (Pt) n+ As the implanted ion source, a high-purity platinum metal target is loaded into the ion source, the ion source is turned on, and the operating parameters are adjusted to obtain a stable beam.

[0014] (3) Vacuuming: Fix the clean PEN film on the injection chamber target stage, close the injection chamber, and start the mechanical pump and molecular turbo pump in sequence to evacuate.

[0015] (4) Ion implantation: Set the implantation parameters and use electrostatic scanning to uniformly scan the ion beam on the target surface; turn on the target stage circulating water cooling system for cooling.

[0016] (5) After the injection is completed, turn off the ion source and wait for the injection chamber to cool to room temperature; slowly fill the injection chamber with high-purity nitrogen gas to atmospheric pressure to obtain the modified PEN film.

[0017] Preferably, the ion source in step (2) of the present invention is a metal vapor vacuum arc (MEVVA) type ion source.

[0018] Preferably, the operating parameters of the ion source in step (2) of the present invention are: arc voltage 20~40V; arc current 50~300A; pulse width 0.2~1ms; pulse repetition frequency 1~50Hz; extraction voltage 20~80kV; more preferably, the operating parameters of the ion source are: arc voltage 30V, arc current (pulse peak) 100A, pulse width 0.5ms, pulse repetition frequency 25Hz; the extraction voltage is set so that its characteristic injection energy is centered at 50keV.

[0019] Preferably, in step (2) of the present invention, a Faraday cup is used to calibrate the beam current density and scanning uniformity of the ion beam in order to monitor the injected dose.

[0020] Preferably, in step (3) of the present invention, the vacuum is drawn down to a pressure <5×10⁻⁶. -4 Pa.

[0021] Preferably, the injection parameters in step (4) of the present invention are: injection energy 30~80keV; injection volume 5×10 15 ~2×10 16 ions / cm 2 Beam current density 0.5 μA / cm 2 An incident angle of 0° means perpendicular incidence.

[0022] Preferably, the scanning frequency in step (4) of the present invention is: 1~2kHz horizontally and 50~100Hz vertically.

[0023] Preferably, the water temperature of the target platform circulating water cooling system in step (4) of the present invention is 15°C.

[0024] Preferably, the purity of the high-purity nitrogen gas in step (5) of the present invention is ≥99.999%.

[0025] Depending on the application requirements, the modified film can be subjected to isothermal heat treatment to improve its performance and long-term stability. The heat treatment conditions are as follows: place the modified film in a tube furnace, and first evacuate to a vacuum of 1×10⁻⁶. - The furnace is heated to 100°C at a rate of 2°C / min under a pressure below 3 Pa or with high-purity argon gas, held for 60 minutes, and then allowed to cool naturally to room temperature. This heat treatment temperature (100°C) is lower than the glass transition temperature of PEN. (121℃) At least 21℃ will not cause irreversible relaxation or thermal deformation of the matrix structure. The heat treatment causes the residual dangling bonds and free radicals in the modified layer to complete the recombination reaction, the carbonized network structure tends to be ordered, the electrical conductivity is further improved and tends to be stable; at the same time, it promotes the short-range diffusion and clustering of Pt atoms, making the size distribution of Pt nanoclusters more uniform and the density of the modified layer more improved. The basic properties described in this invention can be obtained without this heat treatment.

[0026] The principle of this invention: Platinum (Pt) has atomic number Z=78 and atomic mass 195.08 amu, making it one of the most chemically inert elements in the periodic table; PEN (C 14 H 10 The average target atom mass of O4 is 8.65 amu, and that of Pt is... n+ Belonging to the "heavy ion into a light target" system; this extremely high mass ratio leads to two fundamental physical results: at the same injection energy, Pt n+ The projected range of Pt is much shorter than that of light ions, and the same amount of injected energy is compressed into a thinner surface layer, resulting in a significant increase in energy deposition density per unit volume; meanwhile, Pt n+ nuclear energy loss ( It is far superior to light ions and dominates throughout the entire range.

[0027] Pt n+ Nuclear energy loss accounts for 82%–89% of the total energy loss in PENs, generating numerous collisional cascades within each ion track. The transient thermal peaks produced by these collisional cascades reach extremely high temperatures within a very small spatial range (local transient temperatures can reach 1000–2000 K and last for 10 minutes). -11 ~10 -10 (s), this thermal peak promotes the following two simultaneous reactions: Firstly, the ester bonds (-COO-), C / C bonds, and CH bonds in the PEN molecular chain break, releasing carbon atoms, which promotes... Carbon clusters form; as the injection rate increases to the percolation threshold, carbon clusters in adjacent tracks interconnect to form a conductive network, and the surface resistivity decreases to 10. 6 ~10 9 Ω / sq.

[0028] Secondly, due to their extremely high chemical inertness, the implanted Pt atoms do not tend to form stable oxides. Therefore, during the thermal cooling process, Pt atoms tend to aggregate in the modified layer as metallic nanoclusters rather than forming oxides. Simultaneously, metallic Pt itself has extremely strong chemical inertness to atomic oxygen. The Pt nanoclusters enriched on the surface of the modified layer are physically embedded in the carbonized matrix, forming a dense barrier layer that prevents atomic oxygen from eroding the PEN matrix. The entire process is completed in a single ion implantation, requiring no subsequent oxidation treatment, and the modified layer exhibits a continuous gradient distribution along the depth direction.

[0029] This invention provides a method for modifying PEN thin films by single-step implantation of platinum ions, which has the following beneficial effects: (1) This invention modifies PEN films by single-step implantation of platinum ions. Only one implantation is required, and no subsequent oxidation treatment is needed to simultaneously obtain 10 PEN films.6 ~10 9 It exhibits an electrostatic dissipative surface resistivity of Ω / sq and excellent resistance to antigenic oxygen attack.

[0030] (2) The method of the present invention utilizes Pt n+ The nuclear energy loss-dominated (82%–89%) physical characteristics of PENs synchronously drive sp through transient thermal peaks (1000–2000 K) within the ion track. 2 The formation of a carbon cluster conductive network and a dense layer of metal Pt nanoclusters results in a modified layer with a continuous gradient distribution along the depth direction and no abrupt interface with the substrate, thus avoiding the peeling problem of traditional coating methods.

[0031] (3) By utilizing the intrinsic chemical inertness of platinum, the thin film obtained by this invention can achieve both electrical conductivity and atomic oxygen resistance without any post-processing. The process is short, simple, and saves on post-processing. It is suitable for applications such as spacecraft surface materials and electronic packaging that have comprehensive requirements for electrostatic protection and atomic oxygen resistance. Attached Figure Description

[0032] Figure 1 This is the Pt invention n+ A comparative schematic diagram of the cross-sectional structures of the single-step injection modification method and the traditional coating scheme. Figure 1 (a) is a schematic diagram of the cross-sectional structure of a traditional coating scheme. Figure 1 (b) represents Pt n+ A schematic diagram of the cross-sectional structure of the single-step injection modification method.

[0033] Figure 2 These are embodiments 1-6 of the present invention, Pt. n+ Electron blocking ability and nuclear blocking ability of implanted modified PEN thin films (Se) Depth distribution map. Detailed Implementation

[0034] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0035] Example 1 A method for single-step implantation of platinum ions to modify PEN thin films, the specific steps of which are as follows: (1) Target material preparation: Polyethylene naphthalate (PEN) film was used as the target material. Commercially available biaxially stretched PEN film with a thickness of 50 μm and a density of 1.36 g / cm³ was used. 3Keep the material shape unchanged and do not deform it in any way. After cutting the film to the required size, first clean it with acetone using ultrasound for 10 minutes, then clean it with anhydrous ethanol using ultrasound for 10 minutes to remove organic matter and particles from the film surface. Then dry it with high-purity nitrogen (purity ≥99.999%) to obtain a clean PEN film. Place the clean PEN film in a clean container for storage to prevent recontamination.

[0036] (2) Ion source preparation: using platinum ions (Pt) n+ A high-purity platinum metal target is loaded into the ion source as the implantation ion source. Platinum metal has a melting point of 1768.3℃, which is far higher than the operating temperature range of conventional sputtering ion sources. Therefore, a metal vapor vacuum arc (MEVVA) ion source is required to obtain stable Pt. n+ Beam current; turn on the ion source and adjust the operating parameters. The operating parameters of the ion source are: arc voltage 30V, arc current (pulse peak) 100A, pulse width 0.5ms, pulse repetition frequency 25Hz; extract the voltage so that the characteristic injection energy is centered at 50keV; after the beam current stabilizes, use a Faraday cup to calibrate the beam current density and ion beam uniformity.

[0037] (3) Vacuuming: Fix the clean PEN film onto the water-cooled target stage in the injection chamber, ensuring the film surface is flat and in good thermal contact with the target stage; after closing the injection chamber, start the mechanical pump and molecular turbo pump in sequence to perform stepwise vacuuming; wait until the pressure in the injection chamber is <5×10 -4 Injection can only be performed when Pa is present.

[0038] (4) Ion implantation (maintaining the implantation chamber pressure <5×10 during the implantation process) -4 Pa): The injection parameters are set as follows: the injection energy is centered at 50 keV; the injection volume is 1×10⁻⁶. 16 ions / cm 2 Beam current density 0.5 μA / cm 2 Incident angle 0° (vertical incidence); Electrostatic scanning is used to uniformly scan the ion beam on the target surface, with a scanning frequency of 1kHz horizontally and 50Hz vertically (target surface flux uniformity better than ±5%); The target stage circulating water cooling system is turned on, and the water temperature is 15℃; (Pt n+ The nuclear stopping ability is 168.4 eV / Å at 50 keV, and the single-track carbonization efficiency is even higher, 1×10 16 ions / cm 2 The injection volume allows the carbonized network to fully permeate and conduct.

[0039] (5) After the injection is completed, turn off the ion source and wait for the injection chamber to cool to room temperature; slowly fill the injection chamber with high-purity nitrogen to atmospheric pressure, open the injection chamber, and take out the modified PEN film; store the film in a clean sealed bag to avoid contamination by moisture and organic matter in the atmosphere.

[0040] In this embodiment, no subsequent oxidation conversion treatment or heat treatment is performed after injection, and the modified PEN film is obtained directly.

[0041] The surface resistivity of the modified PEN film in this embodiment is 10. 6 ~10 9 The Ω / sq range indicates that the conduction mechanism is driven by nuclear collision cascades. The carbonized network facilitates permeation and conduction; the modified layer surface is enriched with metallic Pt nanoclusters. Metallic Pt has extremely strong chemical inertness to atomic oxygen, and the barrier layer composed of Pt nanoclusters can effectively prevent AO from eroding the PEN matrix. The total thickness of the modified layer is approximately 43 nm (50 keV implantation), with a continuous gradient distribution along the depth and no abrupt interfaces; the outermost layer (0–10 nm) has a high degree of carbonization, high Pt nanocluster density, the lowest resistivity, and the best anti-atomic oxygen performance; the degree of carbonization in the middle region (10–43 nm) varies with depth; at the end of the range, a PEN matrix deeper than 43 nm is used to maintain the original mechanical properties and chemical integrity.

[0042] Pt n+ A nuclear stopping power of 168.4 eV / Å (with Sn accounting for 86.0% of the total energy loss) can be obtained by implantation at 50 keV, and the carbonization efficiency is much higher than that of light ions; at the same time, the metallic Pt nanoclusters have the intrinsic inertness of noble metals to atomic oxygen, and both conductivity and anti-atomic oxygen functions can be achieved in a single step without subsequent processing. The above examples show that using 50 keV and 1×10 16 ions / cm 2 Pt conditions for PEN thin films n+ Single-step injection, without the need for subsequent oxidation conversion treatment, can simultaneously achieve electrostatic dissipative conductivity (surface resistivity at 10). 6 ~10 9 It has improved the resistance to Ω / sq and antigenic oxygen erosion, and there is a continuous gradient structure between the modified layer and the substrate, which avoids the interface peeling problem caused by the coating method.

[0043] Example 2 The difference between this embodiment and embodiment 1 is that the energy injected in step (4) is centered at 30 keV, while the other steps are the same.

[0044] Example 3 The difference between this embodiment and embodiment 1 is that the energy injected in step (4) is centered at 40 keV, while the other steps are the same.

[0045] Example 4 The difference between this embodiment and embodiment 1 is that the energy injected in step (4) is centered at 60 keV, while the other steps are the same.

[0046] Example 5 The difference between this embodiment and embodiment 1 is that the energy injected in step (4) is centered at 70 keV, while the other steps are the same.

[0047] Example 6 The difference between this embodiment and embodiment 1 is that the energy injected in step (4) is centered at 80 keV, while the other steps are the same.

[0048] Comparative Example 1 The difference between this comparative example and Example 1 is that the energy injected in step (4) is centered at 10 keV, while the other steps are the same.

[0049] Comparative Example 2 The difference between this comparative example and Example 1 is that the energy injected in step (4) is centered at 20 keV, while the other steps are the same.

[0050] Comparative Example 3 The difference between this comparative example and Example 1 is that the energy injected in step (4) is centered at 90 keV, while the other steps are the same.

[0051] Comparative Example 4 The difference between this comparative example and Example 1 is that the energy injected in step (4) is centered at 100 keV, while the other steps are the same.

[0052] Based on ZBL theory and LSS transport theory, for Pt n+ Energy loss and range in PEN are calculated, and the specific calculation model and formulas are as follows: (1) Electron energy loss (Lindhard-Scharff, Ziegler-Manoyan effective charge correction) The inelastic interaction between ions and the electron cloud of the target material excites or ionizes the electrons in the target material. In the low-velocity region ( ,in denoted as ion velocity (m / s). (for Bohr's speed) Equivalent to electron energy loss (eV / Å). Proportional to ion velocity: in These are the Lindhard-Scharff coefficients. and These are the atomic numbers of the incident ion and the target atom, respectively. The effective charge fraction of Ziegler-Manoyan. It is the kinetic energy of ions. Ion mass; effective charge fraction Determined by the following formula: in For the reduction rate; for 50 keV Pt n+ , , Substituting into the above formula, we get This means Pt n+ At this energy, the effective charge is only about 21% of its atomic number, and electron energy loss is severely suppressed.

[0053] (2) Nuclear energy loss (Final value, eV / Å) Elastic Coulomb scattering between ions and the target atomic nuclei causes displacement of the target atoms, and the nuclear energy loss is described by the ZBL general nuclear stopping formula; First, calculate the ZBL shielding length: in ZBL shielding length (nm) The Bohr radius (nm); Then calculate the reduced energy. : Reduction of nuclear deterrence ability Given by the ZBL general function: Nuclear stop section (eV·Å² / atom) is: Ultimate nuclear energy loss for: Where N is the atomic number density of the target material ( For PEN, .

[0054] (3) Total nuclear energy loss of the compound target (Bragg summation rule) Total nuclear energy loss in compounds (eV / Å) (and total electron energy loss) according to the atomic fraction of each elemental component Weighted summation: in , It refers to the nuclear energy loss or electronic energy loss of the element under corresponding ion implantation. For PEN ( The total number of atoms is 28, and the fractions of each element are as follows: Therefore, the total nuclear energy loss (eV / Å) is: The same applies to total electron energy loss.

[0055] (4) Projection range (nm) and range discrepancy Calculation of (standard deviation, nm) Projection range It is the average penetration depth of ions in the incident direction, according to LSS transport theory. Total path length can be used The result is calculated using (nm) and the mass ratio correction factor: in ( To completely prevent the ability ; ( The initial kinetic energy is denoted as φ; during numerical calculations, discrete energy step accumulation is used. Projection range With total path length Between by mass ratio Related: in ( ) represents the average atomic mass of the target material. The mass of the incident ions ( ); for Pt n+ Inject PEN, , ,have to , .

[0056] Range discrepancy The standard deviation of the projected range (i.e., the standard deviation of the projected range) is determined by the statistical fluctuations of energy loss; according to LSS theory, its approximate formula is: In the formula This is an empirical correction factor, typically ranging from 0.5 to 0.9. This invention uses... .

[0057] (5) Calculation results Applying the above ZBL formula to Pt n+ Injecting PEN into the system, system calculations were performed on Examples 1-6 and Comparative Examples 1-4 using an energy range of 10-100 keV. The data are shown in Table 1. n+ After injecting PEN and The trend of changes in depth is as follows: Figure 2 As shown.

[0058] Table 1 Pt n+ Energy loss and range data of injected PEN Table 1 shows that, within the energy range of 10–100 keV, Pt n+ In PEN, 81.8% to 91.4% of energy loss occurs through nuclear collisions, with nuclear energy loss being the dominant energy level across the entire energy range.

[0059] As can be seen from Table 1, there is a core contradiction in energy selection: the lower the energy, the higher the proportion of nuclear energy loss (at 10 keV). (Accounting for 91.4%), the near-surface collision cascade density is higher; however, the thinner the modified layer (at 10 keV), the greater the density. With a thickness of only 17.9 nm, it is not conducive to the formation of a complete conductive percolation network and gradient structure; the higher the energy, the thicker the modified layer (at 100 keV). =66.0 nm), but the proportion of nuclear energy loss decreased (at 100 keV). (81.8%), and the thermal load of the ion beam on the PEN target increases.

[0060] The calculation results above reveal Pt n+ The core physical mechanism of PEN implantation modification is fundamentally different from that of light ion implantation; a large-scale collisional cascade driven by nuclear energy loss generates a transient thermal peak, simultaneously driving two synchronous reactions within the extremely small space of the ion track: the formation of a carbonized conductive network and the generation of Pt metal nanoclusters; at an energy of 50 keV, a single Pt... n+ Upon impact with the PEN surface, a large number of nuclear collision cascades are induced within its projected range (approximately 43 nm). Each nuclear collision transfers the kinetic energy of the incident ion to the target atom, which is then ejected and collides with neighboring atoms, forming a cascade process; this process lasts for approximately 10... -13 ~10 -12The collision cascade region generates a nanoscale columnar high-energy deposition region around the ion track; the total energy deposited within a 43 nm range is approximately 50 keV, of which about 86% (i.e., 43 keV) originates from nuclear collisions. The effective lateral extension diameter of the collision cascade region is approximately 2-3 nm, and the transient energy density within the region can reach several eV to over ten eV / atom; this transient energy density is much greater than the dissociation energies of all covalent bonds in the PEN molecule (CC bond: 3.6 eV, CO ester bond: 3.7 eV, CH bond: 4.3 eV), therefore the PEN molecular chain is completely broken within the collision cascade region. After the collision cascade ends (approximately 10... -12 During the peak thermal phase (s), the local temperature instantaneously reaches 1000~2000 K, far exceeding the thermal decomposition temperature of PEN (approximately 400~420 ℃, i.e., 673~693 K, with the main degradation peak at 433 ℃), and remains at this temperature for about 10 seconds. -11 ~10 -10 Within this high-temperature window, atoms are in an extremely active state of recombination; during the thermal peak, the broken PEN molecular chain fragments and the injected Pt atoms undergo two different chemical recombination processes.

[0061] Process 1: Formation of the carbonized conductive network: Repeating units of PEN The middle carbon content is 50.0 at.%. The naphthalene ring structure of PEN itself consists of two fused benzene rings. Carbon skeleton; when the PEN molecular chain is broken by nuclear collisions, the released carbon atoms undergo thermal reactions driven by high temperatures. Hybridization transformation, forming graphite-like materials Carbon clusters. With increasing flux, more and more ion tracks overlap, and adjacent tracks... Carbon clusters gradually connect, forming a conductive network when the percolation threshold is reached. Due to Pt n+ of (168.4 eV / Å at 50 keV) is much higher than that of light ions, Pt n+ The degree of carbonization caused in each track is much higher than that of light ions, so the minimum flux required to achieve percolation conductivity is expected to be smaller.

[0062] The critical condition for conductive seepage can be described by classical seepage theory: in For the injection volume, The critical seepage injection rate, The scaling factor for conductivity after seepage. Critical index (three-dimensional seepage) Two-dimensional extraction For Pt n+The injected extremely shallow modified layer (thickness < 60 nm) exhibits percolation behavior close to two-dimensional.

[0063] Process 2: In-situ formation of Pt metal nanoclusters: Platinum is a typical noble metal, and the standard enthalpy of formation of PtO2... Only about The Pt-O bond dissociation energy is 80 kJ / mol, much lower than that of many common metal oxides. The Pt-O bond dissociation energy is 246 kJ / mol, a value that remains approximately constant under different coordination numbers and platinum valence states. These values ​​indicate that Pt does not thermodynamically have a strong tendency to form stable oxides with oxygen. After the nuclear collision breaks the PEN molecular chain, releasing oxygen atoms and carbon skeleton fragments, the injected Pt atoms undergo the following main processes during the cooling process from the thermal peak: Formation of Pt metal nanoclusters: The Pt-Pt metal bond energy is 357.3±15.1 kJ / mol. During the cooling process of the thermal peak, Pt atoms tend to aggregate to form metallic nanoclusters. Unlike organic polymers, the surface of metallic Pt does not generate volatile oxidation products (such as CO and CO2) under atomic oxygen bombardment, but maintains a stable metallic state, which is also the characteristic of Pt. n+ The core mechanism by which the injection method achieves antigen oxygenation performance.

[0064] Furthermore, because Pt n+ The range of the injection is very short (30~80 keV corresponds to 32~57 nm), and the injected Pt is mainly distributed near the surface. Vacancy-assisted diffusion caused by nuclear collisions causes some Pt ​​atoms to migrate to the outermost surface position, thereby increasing the Pt concentration in the outermost layer.

[0065] The two processes occur simultaneously: the carbonization reaction and the formation of Pt metal nanoclusters, driven by nuclear collision cascades and subsequent thermal peaks, occur within the same spatial region (within the ion track) and the same time window (10). -12 ~10 -10 This process is completed simultaneously within s), which is the physical basis for "single-step injection and multi-functional modification".

[0066] Pt n+ The modified layer formed after PEN injection has a continuous gradient structure from the surface to the substrate, rather than the abrupt interface found in coating methods. This is a natural consequence of the continuous variation of energy deposition density along depth.

[0067] According to ZBL calculations, 50 keV Pt in Example 1 n+ When injecting PEN, It is highest at the incident surface, and decreases monotonically with depth, at the projected range. The concentration of implanted Pt atoms decays to zero near 43 nm; the concentration distribution of implanted Pt atoms is as follows: The peak value is reached nearby; the modified layer forms the following gradient structure along its depth: (1) Surface region (0~10 nm): It has the highest degree of carbonization and is also the region where Pt atoms are segregated and enriched on the surface through vacancy-assisted diffusion. The Pt nanoclusters have the highest density, resulting in the lowest resistivity and the strongest anti-AO performance.

[0068] (2) Intermediate region (10~43 nm): As the depth along the path decreases, the degree of carbonization also decreases; the Pt atom concentration increases from low to high. The nearby peaks form a continuous transition between the conductive and insulating layers.

[0069] (3) The end of the range is at a depth (>43 nm): As the concentration decays to zero, the Pt concentration quickly drops to a negligible level, while the mechanical properties and chemical composition of the PEN matrix remain unchanged.

[0070] In summary, PEN films... At only 121°C, this invention combines 30~80 keV with a low beam current density ( The water-cooled target stage ensures that the temperature of the PEN film is much lower than that of the target stage. This will not cause thermal deformation of the substrate. If the energy is too high, exceeding 100keV, it will greatly increase the difficulty of beam heat load control. The continuous gradient structure ensures that there is no abrupt interface between the modified layer and the PEN substrate, preventing interface delamination problems caused by mismatch in thermal expansion coefficients in coating methods.

[0071] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for single-step implantation modification of PEN thin films with platinum ions, characterized in that, Specifically, the following steps are included: (1) Target preparation: Polyethylene naphthalate film was used as the target material. It was cleaned and dried to obtain a clean PEN film. (2) Ion source preparation: Using platinum ions as the implantation ion source, a high-purity platinum metal target is loaded into the ion source, the ion source is turned on, and the working parameters are adjusted to obtain a stable beam. (3) Vacuuming: Fix the clean PEN film on the injection chamber target stage, close the injection chamber, and start the mechanical pump and molecular turbo pump in sequence to evacuate the vacuum. (4) Ion implantation: Set the implantation parameters and use electrostatic scanning to uniformly scan the ion beam on the target surface; Turn on the target platform's circulating water cooling system for cooling; (5) After the injection is completed, turn off the ion source and wait for the injection chamber to cool to room temperature; slowly fill the injection chamber with high-purity nitrogen gas to atmospheric pressure to obtain the modified PEN film.

2. The method for single-step implantation modification of PEN thin films with platinum ions according to claim 1, characterized in that, The ion source mentioned in step (2) is a metal vapor vacuum arc (MEVVA) type ion source.

3. The method for single-step implantation modification of PEN thin films with platinum ions according to claim 1, characterized in that, In step (2), a Faraday cup is used to calibrate the beam current density and scanning uniformity of the ion beam in order to monitor the injected dose.

4. The method for single-step implantation modification of PEN thin films with platinum ions according to claim 1, characterized in that, The operating parameters of the ion source in step (2) are: arc voltage 20~40V; arc current 50~300A; pulse width 0.2~1ms; pulse repetition frequency 1~50Hz; extraction voltage 20~80kV.

5. The method for single-step implantation modification of PEN thin films with platinum ions according to claim 1, characterized in that, The step (3) involves evacuating the vacuum until the pressure is <5×10. -4 Pa.

6. The method for single-step implantation modification of PEN thin films with platinum ions according to claim 1, characterized in that, The injection parameters mentioned in step (4) are: injection energy 30~80keV; injection volume 5×10 15 ~2×10 16 ions / cm 2 Beam current density 0.5 μA / cm 2 An incident angle of 0° means perpendicular incidence.

7. The method for single-step implantation modification of PEN thin films with platinum ions according to claim 1, characterized in that, The scanning frequency in step (4) is: 1~2 kHz horizontally and 50~100 Hz vertically.

8. The method for single-step implantation modification of PEN thin films with platinum ions according to claim 1, characterized in that, The target platform circulating water cooling system in step (4) has a water temperature of 15°C.

9. The method for single-step implantation modification of PEN thin films with platinum ions according to claim 1, characterized in that, The purity of the high-purity nitrogen gas mentioned in step (5) is ≥99.999%.